“The Appearances of Yoni” in Ancient Lanna Manuscripts: The Power Relations between Men and Women - Thammathi, Phuangphaka (Connexion: Journal of Humanities and Social Sciences, 2021)
This research aims to study the beliefs about “yoni” (external female genitalia) described in ancient Lanna manuscripts [pap-saa and palm-leaf] total 30 pieces and to examine the power relations between men and women. There are four types of beliefs as follow: (1) family relations (2) family’s socioeconomic and social status (3) the appearances of yoni concerning sexual behavior and (4) the beauty of yoni relates to men’s ideology. In part of the power relations between men and women, four dominant areas were categorized and analyzed respectively which are knowledge, belief, economic, and social space. It is also found that women have fewer power relations than men in terms of knowledge and social spaces. On the contrary, women have more power relations than men in terms of belief and economic spaces.